Life to the extreme : how a chaotic kid became America's favorite carpenter - Pennington, Ty, 1965-; Thrasher, Travis, 1971- (Zondervan, 2019)
"The star of Extreme Makeover: Home Edition and Trading Spaces, Ty Pennington, shares his life story - lessons he's learned while serving others, random acts of kindness, battling ADHD in a busy career, and anecdotes from behind the scenes of America's favorite home shows"--